Where art belongs - Kraus, Chris (Los Angeles : Semiotext(e), 2011)
"In Where Art Belongs, Chris Kraus examines artistic enterprises of the past decade that reclaim the use of lived time as a material in the creation of visual art. In four interlinked essays, Kraus expands the argument begun in her earlier book Video Green that 'the art world is interesting only insofar as it reflects the larger world outside it.' Moving from New York to Berlin to Los Angeles to the Pueblo Nuevo barrio of Mexicali, Kraus addresses such subjects as the ubiquity of video, the legacy of the 1960s Amsterdam underground newspaper Suck, and the activities of the New York art collective Bernadette Corporation. She examines the uses of boredom, poetry, privatized prisons, community art, corporate philanthropy, vertically integrated manufacturing, and discarded utopias, revealing the surprising persistence of microcultures within the matrix"--Publisher's description.
1. No more utopias. You are invited to be the last tiny creature -- The complete poem, Bernadette Corporation -- No more utopias -- 2. Body not apart. May '69 -- Detour -- Description over plot -- 3. Matrix. Long century -- Indelible video -- Untreated strangeness -- 4. Drift. Twelve words, nine days -- The failed collective.
boek